Russian conservatism in the Putin presidency: The dispersion of a hegemonic discourse - Sergei Prozorov (Danish Institute for International Studies (DIIS), 2004)
The article seeks to map the emergent discursive field of conservatism in Russian politics in the context of the reshapement of the political space in the Putin presidency. In the course of Putin's first presidential term `conservatism' became a privileged mode of political selfidentification in the Russian discourse, functioning as the nodal point of the hegemonic project of the Presidency. Yet, in accordance with the Foucauldian understanding of discourse as a system of dispersion, the article demonstrates the way the conservative discourse is internally fractured into two antagonistic strands, identified by their practitioners as liberal and left conservatisms. While the liberal-conservative orientation supports and sustains the depoliticising project of the Putin presidency, which orders and stabilises the effects of the anti-communist revolution, left conservatism functions in the modality of radical opposition to the Putinian hegemony, thereby contributing to the pluralisation of political space in contemporary Russia. In the present Russian political constellation `conservatism' is therefore less a name for a stable hegemonic configuration than a designator of the field of political struggle over the very identity of postcommunist Russia. The article concludes with a critical discussion of the relation the two strands of Russian conservatism establish to the period of the 1990s as the `moment of the political' in the Russian postcommunist transformation.
Keywords: 330